Effect of steel reinforcement with different degree of corrosion on degeneration of mechanical performance of reinforced concrete frame joints (Fracture and Structural Integrity, 2015)
Beam-column joints which shoulders high-level and vertical shearing effect that maintains balance of beam and column end is the major component influencing the performance of the whole framework. Post earthquake investigation suggests that collapse of frame structure is induced by failure of joints in most cases. Thus, beam-column joints must have strong bearing capacity and good ductility, and reinforced concrete structure just meets the above requirement. But corrosion caused by long time use of reinforced concrete framework will lead to degeneration of mechanical performance of joints. To find out the rule of effect of steel reinforcement with different corrosion rate on degeneration of bearing capacity of reinforced concrete framework joints, this study made a nonlinear numerical analysis on fifteen models without stirrup in the core area of reinforced concrete frame joints using displacement method considering axial load ratio of column end and constraint condition. This work aims to find out the key factor that influences mechanical performance of joints, thus to provide a basis for repair and reinforcement of degenerated framework joints.
Keywords: Reinforced concrete; Mechanical performance of joints; Corrosion of steel reinforcement